Animal Husbandry across the Western Roman Empire: Changes and Continuities. (17th July 2017) - Valenzuela-Lamas, Silvia; Albarella, Umberto
Abstract : This special issue of the European Journal of Archaeology discusses aspects of animal husbandry in a number of provinces of the Western Roman Empire. In this introduction, we describe the general characteristics of animal husbandry in pre-Roman and Roman times to assess any changes that may have occurred after the Roman conquest. The results suggest that the territoriality typifying the first millenniumbc had a significant impact on production, resulting in a decrease in cattle size and frequencies across Europe. Nevertheless, not all the regions reacted in the same way, and regional communities that focused their animal production on pigs implemented more sustainable husbandry practices over time. By bringing together studies carried out across Europe, this journal issue highlights the existence of cases of both change and continuity across the Empire, and the (uneven) impact of the market economy on animal husbandry and dietary practices in climatically different regions. Abstract : Ce numéro spécial de la revue European Journal of Archaeology est consacré à l'élevage dans les provinces de l'Empire romain d'Occident. Cette introduction sert de description des traits généraux de l'élevage aux époques préromaines et romaines et nous permet d'évaluer les changements qui auraient pu avoir lieu après la conquête romaine. Les résultats suggèrent que la territorialité qui marquait le premier millénaire av. J.-C eut une profonde influence sur l'exploitation des animaux domestiques, avec une réduction de la taille et l'apport des bovins à travers l'Europe. Cependant toutes les régions n'ont pas réagi de la même manière et les communautés qui se sont concentrées sur l'élevage des porcs ont mis en œuvre des pratiques d'élevage plus durables au cours du temps. Ce numéro spécial met l'accent sur des cas de transformation et de continuité à travers l'empire romain par l'entremise d'études de cas provenant de diverses régions d'Europe et met en évidence les effets (inégaux) de l'économie de marché sur l'élevage et les habitudes alimentaires dans des régions aux climats différents. Translation by Madeleine Hummler Abstract : Diese Sonderausgabe der Zeitschrift European Journal of Archaeology ist der Tierhaltung in verschiedenen Provinzen des weströmischen Reiches gewidmet. Diese Einleitung beschreibt die allgemeinen Eigenschaften der Viehzucht in der vorrömischen und römischen Zeit, um die Veränderungen, die nach der römischen Eroberung stattgefunden hätten, zu bewerten. Die Ergebnisse zeigen, dass die Territorialität, die das erste vorchristliche Jahrtausend gekennzeichnet, einen maßgeblichen Einfluss auf die Tierproduktion hatte, die eine Minderung der Größe und Anteils der Rinder in Europa zu Folge hatte. Alle Gebiete haben aber nicht gleich reagiert und regionale Gemeinschaften, die sich auf die Schweinezucht konzentrierten, haben im Laufe der Zeit nachhaltigere Tierhaltungspraktiken entwickelt. Durch die Zusammenführung von Fallstudien aus ganz Europa betont diese Sondernummer, dass es im römischen Reich Fälle sowohl von Wechsel wie von Kontinuität gab und, dass der Einfluss der Marktwirtschaft auf die Tierhaltung und die Ernährungsgewohnheiten in klimatisch verschiedenen Gebieten ungleich war. Translation by Madeleine Hummler